(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Finding one’s own voice that could merge a traditional artistic system and the demands of contemporary times is one of the most significant challenges faced by corporeal mime artists. Just over three decades after the passing of Étienne Decroux, what are the strategies devised by post-Decrouxian mimes to meet those demands? The article highlights some strategies contemporary mimes employ to deal with the friction between the system and their own artistic expression. Transporting as devised, incorporating different techniques, and exploring creative principles are some of those strategies that could also apply to other artistic practices based on master-apprentice relationships.